Changes in plasma ghrelin and leptin levels in patients with peptic ulcer and gastritis following eradication of Helicobacter pylori infection. Issue 1 (December 2016) - Kasai, Chika; Sugimoto, Kazushi; Moritani, Isao; Tanaka, Junichiro; Oya, Yumi; Inoue, Hidekazu; Tameda, Masahiko; Shiraki, Katsuya; Ito, Masaaki; Takei, Yoshiyuki; Takase, Kojiro
Abstract Background Helicobacter pylori (H. pylori ) infection and eradication therapy have been known to influence gastric ghrelin and leptin secretion, which may lead to weight gain. However, the exact relationship between plasma ghrelin/leptin levels andH. pylori infection has remained controversial. The aim of this study was to investigate plasma ghrelin and leptin levels inH. pylori -positive and -negative patients, to compare the two levels of the hormones before and afterH. pylori eradication, and to examine the correlation between body mass index (BMI) and active ghrelin or leptin levels, as well as that between atrophic pattern and active ghrelin or leptin levels. Methods Seventy-twoH. pylori -positive patients who underwent upper gastrointestinal endoscopy, 46 diagnosed as having peptic ulcer and 26 as atrophic gastritis, were enrolled. Control samples were obtained from 15 healthyH. pylori -negative volunteers. The extent of atrophic change of the gastric mucosa was assessed endoscopically. Body weight was measured and blood was collected before and 12 weeks afterH. pylori eradication therapy. Blood samples were taken between 8 and 10 AM after an overnight fast. Results Plasma ghrelin levels were significantly lower inH. pylori -positive patients than inH. pylori -negative patients. In particular, plasma active ghrelin levels were significantly lower in patients with gastritis compared with patients with peptic ulcer. Plasma ghrelin levels decreased afterH. pylori eradication in both peptic ulcer and gastritis patients, while plasma leptin levels increased only in peptic ulcer patients. Plasma leptin levels and BMI were positively correlated, and active ghrelin levels and atrophic pattern were weakly negatively correlated in peptic ulcer patients. Conclusion H. pylori infection and eradication therapy may affect circulating ghrelin/leptin levels. This finding suggests a relationship between gastric mucosal injury induced byH. pylori infection and changes in plasma ghrelin and leptin levels.